2020
DOI: 10.1371/journal.pntd.0007755
|View full text |Cite
|
Sign up to set email alerts
|

Mapping the S1 and S1’ subsites of cysteine proteases with new dipeptidyl nitrile inhibitors as trypanocidal agents

Abstract: The cysteine protease cruzipain is considered to be a validated target for therapeutic intervention in the treatment of Chagas disease. A series of 26 new compounds were designed, synthesized, and tested against the recombinant cruzain (Cz) to map its S1/S1ś ubsites. The same series was evaluated on a panel of four human cysteine proteases (CatB, CatK, CatL, CatS) and Leishmania mexicana CPB, which is a potential target for the treatment of cutaneous leishmaniasis. The synthesized compounds are dipeptidyl nitr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…Figure shows the putative binding mode of 2a–c , where essential hydrogen bonds are observed between the ligands and the main chain from Gly68 and Asp162 in the hCatL active site. These fundamental interactions are commonly observed for peptidomimetics interacting with hCatL . It is also worth mentioning that the single-atom modification observed in 2a–c is located at the P3 group (Figure ), where the aromatic ring is to a large extent exposed to the solvent environment.…”
Section: Results and Discussionmentioning
confidence: 60%
See 2 more Smart Citations
“…Figure shows the putative binding mode of 2a–c , where essential hydrogen bonds are observed between the ligands and the main chain from Gly68 and Asp162 in the hCatL active site. These fundamental interactions are commonly observed for peptidomimetics interacting with hCatL . It is also worth mentioning that the single-atom modification observed in 2a–c is located at the P3 group (Figure ), where the aromatic ring is to a large extent exposed to the solvent environment.…”
Section: Results and Discussionmentioning
confidence: 60%
“…These fundamental interactions are commonly observed for peptidomimetics interacting with hCatL. 66 It is also worth mentioning that the single-atom modification observed in 2a−c is located at the P3 group (Figure 2), where the aromatic ring is to a large extent exposed to the solvent environment. Therefore, one can assume that the P3 group is not involved in critical interactions in the active site of hCatL.…”
Section: ■ Methodsmentioning
confidence: 63%
See 1 more Smart Citation
“…[4] The extensive research around K777 has provided a status of "validated target" for cruzain, which has led several research groups to explore cruzain inhibitors as potential new treatments for Chagas disease. [16][17][18][19][20] However, despite the essentiality of cruzain for the T. cruzi life cycle, it has been observed in several cases a lack of translation from in vitro cruzain activity to T. cruzi biological activity (both in vitro and in vivo). [19,[21][22][23][24] Some studies have suggested that reversible cruzain inhibitors would be less likely to present trypanocidal activity.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, it is recognized by the host as an antigen and modulates the host macrophage response. , Tbr CATL is important for penetration through the blood–brain barrier and is essential for parasite survival. ,, Efforts to develop inhibitors have led to the discovery of many potent chemotypes against both proteases (reviewed in refs , , and ). Recently reported inhibitors include peptidomimetics and nonpeptidic small molecules that inhibit the enzymes irreversibly or reversibly. In addition to their efficacy in in vitro assays against trypanosomes, ,,, cysteine protease inhibitors have shown efficacy in mice and dog models of Chagas disease, and to reduce parasitemia and/or increase survival ,, in mouse models of T. brucei infection.…”
Section: Introductionmentioning
confidence: 99%